(untitled) (The Research of Medical Science Review, 2025)
This case report presents the clinical profile, assessment, and therapeutic intervention of a 46-year-old male diagnosed with Severe Opioid Use Disorder and a Severe Single Episode of Major Depressive Disorder, accompanied by parent-child and sibling relational problems. The patient exhibited a long history of heroin dependence, compounded by socio-emotional stressors, including unresolved familial conflicts and financial hardship. Initial symptoms included persistent low mood, impaired memory, reduced occupational functioning, and physical complaints such as abdominal pain, nausea, and general weakness. Psychometric assessments, including the MSE, DAST-10, BDI-II, PCRS, and SRQ, were administered to evaluate substance use and depressive symptomatology. A structured intervention plan based on motivational interviewing, relapse prevention strategies, and cognitive-behavioral techniques was implemented during inpatient care. The therapeutic process followed the stages of the change model, with sessions targeting self-esteem enhancement, emotional regulation, and psychosocial support. Significant improvement was noted in the patient's mood, motivation for recovery, and family involvement. The case highlights the importance of integrating biopsychosocial approaches and family psychoeducation in the management of co-occurring substance use and depressive disorders.